ISLAMIC RELIGIOUS CHARACTER DEVELOPMENT MANAGEMENT THROUGH MATRICULATION - Firmansyah, Abd. Mu'iz (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The purpose of this study is intended to describe the management of fostering the characteristics of students through matriculation. This research uses a qualitative approach with a case study method. The subjects of this study were the Head of Madrasah, Student Affairs Coordinator, Curriculum Coordinator, Teachers, Homeroom Teachers, and Students. Data collection techniques using interviews, observation, and documentation. The results of this study indicate that 1) the management of Islamic religious character development that is implemented at MI Miftahul Ulum is mentoring and direct monitoring in the habituation of 12S in an orderly manner supported by their respective homeroom teachers; 2) The implementation of fostering Islamic religious character at MI Miftahul Ulum integrates the National curriculum with the internal curriculum developed by madrasas in terms of matriculation. In addition, there are programs for fostering Islamic religious character by exemplifying intra and extra activities that can create a madrasa climate in accordance with the vision and mission. 3) The main supporting factors related to the development of Islamic religious character at MI Miftahul Ulum are educators who behave according to the guidance of the Conception of educators as role models who have good morals in everyday life.